Sensory and chemical characteristics of tomato juice from fresh market cultivars with comparison to commercial tomato juice. (22nd September 2020) - Koltun, Stephen J.; MacIntosh, Andrew J.; Goodrich‐Schneider, Renee M.; Klee, Harry J.; Hutton, Samuel F.; Sarnoski, Paul J.
Abstract: Florida tomatoes are primarily produced for the fresh market and have not been widely used in processed tomato products. This study tested six Florida fresh market tomato cultivars (FLA 8083, FLA 8297, FLA 8344, FLA 8570, FLA 8924 and Garden Gem) to determine suitability for juice production. Genetic and environmental‐induced variation was studied, and analyses identified metabolites that influenced the perceptual and hedonic responses of tomato juice. Each cultivar was processed into juice by hot breaking at 86 ˚C for 3.5 minutes and then pasteurization at 121 ˚C for 42 seconds for a shelf stable product. Among the six pilot products, FLA 8344 cultivar had significantly higher soluble solids content and titratable acidity in all three experiments. The pH of each of the tomato juices made from fresh market tomatoes was within or below the typical range for tomato juice. Garden Gem was consistently rated significantly ( P  ≤ .05) higher for aroma, overall liking, tomato flavour, texture and overall flavour. In all three experiments, tomato juice from a fresh market cultivar simultaneously had the greatest abundance of green‐note volatiles (hexanal, 1‐hexanol, (Z)‐3‐hexen‐1‐ol, etc) and the lowest abundance of cooked‐note volatiles (dimethyl sulphide, methional and furfural). Consumer acceptance increased as salt concentration increased and while season had minor effects on the chemical composition of the juice, consumers preferred the Spring processed tomato juice over Fall. Abstract : Study design for comparing fresh market tomato juice with commercial tomato juice.